Analisis Komparasi Elevasi DEMNAS dan ASTER GDEM Terhadap Hasil Survei Terestris - Soraya Irene Lumbantoruan; Pintanugra Persadanta; Willy Adrian (Fakultas Teknik Transportasi dan Logistik Trisakti, 2023)
The airport feasibility study is crucial for new airport proposals, serving as a prerequisite for determining the airport location. A key aspect of this study is assessing the construction's technical feasibility, particularly analyzing the topography of the proposed site. Topographic evaluation necessitates a terrestrial survey, known for its high precision as it's conducted directly on-site. However, this method is resource-intensive in terms of time, energy, and finances. Alternatively, DEMNAS and ASTER GDEM offer a cost-effective approach, providing comparable data with 8-meter and 30-meter spatial resolution, respectively. Analyzing their data against terrestrial surveys for a new airport site in Mahakam Ulu Regency, DEMNAS demonstrated an average elevation difference of 2.04 meters, whereas ASTER GDEM showed 8.89 meters. Validity and accuracy tests indicated that DEMNAS outperformed ASTER GDEM, showcasing a superior R2 value of 0.963 compared to 0.674, and lower RMSE of 2.417 meters versus 6.244 meters. The results suggest that DEMNAS, with its accuracy and efficiency, is a viable alternative for assessing the topographic conditions of potential airport sites, aiding in the preparation of comprehensive airport feasibility studies.